Penerapaan Model Problem Based and Learning Dalam Meningkatkan Hasil Belajar dan Sikap Gotong Royong Berbantuan Media Audio Visual - Irene Agustin (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2023)
Abstract. The Problem Based Learning learning model is a learning method that is triggered by problems, which encourages students to learn and work cooperatively in groups to obtain solutions, think critically and analytically, and be able to determine and use appropriate learning resources. This research is classroom action research in the application of the Problem Based Learning Model with the help of Audio Visual Media. The aim of the research is to describe the Problem Based Learning learning model to improve student learning outcomes and mutual cooperation attitudes in Phase A class II at SDN Slembaran Surakarta. The research procedure follows the PTK flow, namely starting from planning (compiling lesson plans, learning tools, observation sheets, and evaluation instruments), research implementation (application of the Problem Based and Learning Model with the help of visual audio media), evaluation (test at the end of each learning cycle using test instruments, and mutual cooperation through observation). The data obtained was analyzed using descriptive quantitative analysis. The results of research carried out on 6 students achieved classical completion in cycle I with an average of 66, which is 50% shows that there are 3 students who got a score above 70, and 3 students does not meet completeness standards. Then in cycle II with the achievement of completeness The average is 100%, which shows that all 6 students meet the standards completeness, the application of the Problem Based and Learning Model is effective in improving learning outcomes and mutual cooperation attitudes assisted by audio visual media for Phase A Class II students at SDN Slembaran Surakarta for the 2023/2024